Strategic Approaches of Islamic Banks in Developing Digital Murabahah: Evidence from Mandailing Natal - Siti Kholijah (Fakultas Ekonomi dan Bisnis Islam, 2025)
This paper examines the adoption of Digital Murabahah in Mandailing Natal within the broader context of digital transformation in Islamic banking, emphasizing its potential to enhance financial accessibility while maintaining Sharia compliance. Although digital initiatives have rapidly advanced in major Islamic financial institutions, limited attention has been given to their development in regional and rural contexts, creating a significant research gap in understanding localized implementation challenges. Addressing this gap, the study investigates the key barriers and strategic solutions for developing Sharia-compliant digital financing at the regional level. This study contributes novelty by focusing on regional Islamic banking dynamics, an area often overlooked in existing research dominated by large-scale banking contexts. Using a qualitative approach, this research draws on secondary data from Islamic banking reports, regulatory documents, and recent academic studies, supported by comparative case analyses of Islamic banks implementing Digital Murabahah. The findings reveal that limited digital infrastructure, low customer literacy, and complex regulatory frameworks impede adoption, with larger Islamic banks advancing faster than regional ones. The study contributes to existing literature by providing a region-specific analysis of digital Islamic finance transformation and proposing a strategic framework that integrates fintech collaboration, customer education, and adaptive regulatory support. It concludes that a gradual transition through hybrid banking models—aligned with technological readiness and regulatory reform—is crucial for strengthening financial inclusion and ensuring the sustainable growth of Islamic banking in regional economies.